Preparation and luminescent properties of multicolored SrAl2O4:Eu2+, Dy3+/SiO2-coated red-emitting coumarin color converter/polyamide 6 luminous fiber with warm-toned luminescence. Issue 15 (August 2020) - Chen, Zhi; Cheng, Qing; Ke, Huizhen; Li, Yonggui; Wei, Qufu; Ge, Mingqiao
Novel SrAl2 O4 :Eu 2+, Dy 3+ /SiO2 -coated red-emitting coumarin color converter (SiO2 @RECC)/polyamide 6 (PA6) luminous fibers with warm-toned luminescence color were prepared on the basis of the energy transfer and color conversion from SrAl2 O4 :Eu 2+, Dy 3+ to RECC. The mass concentrations of RECC used in the fibers were adjusted to obtain different luminescence colors. Scanning electron microscopy images, photoluminescence (PL) emission spectra, RGB color coordinates, luminescence photos, and luminescence lifetimes were analyzed. Results demonstrated that the PL emission spectra of luminous fibers contain two emission peaks in the range of 475–700 nm. The increase in RECC concentration contributed to the gradual redshift of the second emission peak, and the ratio of the second emission maximum to the first emission maximum also increased gradually. The luminescence color of the fibers shifted gradually toward red in the dark. Moreover, the fibers showed light yellow, yellow, orange, and orange-reddish luminescence in the dark when the mass concentrations of RECC were fixed at 0.1%, 0.6%, 1.0%, and 1.4%, correspondingly. The luminescence lifetimes of the fibers can be sustained for at least 13, 288 s. The prepared warm-toned SrAl2 O4 :Eu 2+, Dy 3+ /SiO2 @RECC/PA6 luminous fibers have considerable application prospects, given their excellent luminescence properties.